1985
DOI: 10.1021/ac00290a049
|View full text |Cite
|
Sign up to set email alerts
|

Model studies on multiple channel analysis of free magnesium, calcium, sodium, and potassium at physiological concentration levels with ion-selective electrodes

Abstract: Simultaneous analysis of free metal ion concentrations with ion-selective electrodes (ISEs) may be achieved even for nonspecific sensors. This Is demonstrated for the determination of Ca2+, Mg2+, K+, and Na+ Ions at concentrations typical of Intracellular, urine, or serum levels based on calibrations with standards of mixtures of the metal ions rather than just single metal Ion containing solutions. The advantages of data reduction by means of partial least squares (PLS) In principal components compared to ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(83 citation statements)
references
References 12 publications
1
82
0
Order By: Relevance
“…The study was linked to sodium and potassium ISE studies on blood and urine [52]. Close to this are chemometric type model studies on multiple channel analysis of free magnesium, calcium, sodium, and potassium at physiological concentration levels [53,54].…”
Section: Researches On Calcium Isesmentioning
confidence: 99%
“…The study was linked to sodium and potassium ISE studies on blood and urine [52]. Close to this are chemometric type model studies on multiple channel analysis of free magnesium, calcium, sodium, and potassium at physiological concentration levels [53,54].…”
Section: Researches On Calcium Isesmentioning
confidence: 99%
“…An ISE measures solution potential (see for instance [6]) which is related to the free primary ion activity by the Nernst equation (1), but can also be related to the free interfering ion activity by the Nikolskii relation (2) according to the IUPAC recommendations [7].…”
Section: Ion-selective Electrode Theorymentioning
confidence: 99%
“…Otto et al [1] showed that an over-determined approach of the problem for multiple ion determinations is feasible with Ca 2+ , Mg 2+ , Na + , K + . Beebe et al [2][3] stated that using an array of sparingly selective electrodes gives better results than using an array of highly selective electrodes (use of non linear multiple regression, for Na + , K + ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1985, Otto and Thomas presented the first e-tongue system (Otto and Thomas 1985). The inspiration behind the design and operation of electronic tongues (ET) systems is the neurophysiology of the senses of taste.…”
Section: Introductionmentioning
confidence: 99%